Sc, Zr micro-alloyed Al-Mn-Cu heat-resistant aluminum alloy, preparation method and application thereof

CN122879569APending Publication Date: 2026-10-09QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611172623.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]目前市面主流耐热铝合金分为 Al-Si、Al-Cu、Al-Mg 三大体系,但当下高端装备热端零部件的服役工况逐步提升至300℃以上,传统合金体系的高温强度、抗蠕变性能快速衰减,已无法适配严苛高温使用需求

Benefits of technology

(1)本发明通过在Al-Mn-Cu合金中添加Sc、Zr元素形成L12-Al3(Sc,Zr)相,L12-Al3(Sc,Zr)纳米析出相因其与铝基体完全共格的特点而受到广泛关注。其在铝基体中优先析出L12-Al3(Sc,Zr)纳米颗粒的特性,为T相提供高密度异质形核衬底。可显著降低T相形核能垒,使其在较低温度下大量形核;同时,L12相的空间钉扎效应有效抑制T相在高温下的Ostwald粗化,促进T相更小更弥散地析出,显著提升合金强化效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879569A_ABST
    Figure CN122879569A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of aluminum alloy, and particularly relates to a Sc and Zr micro-alloyed Al-Mn-Cu heat-resistant aluminum alloy and a preparation method and application thereof. The application forms L12-Al3(Sc, Zr) phase by adding Sc and Zr elements in the Al-Mn-Cu alloy, and the L12-Al3(Sc, Zr) nano precipitated phase is widely concerned due to its complete coherence with the aluminum matrix. The characteristics of preferentially precipitating L12-Al3(Sc, Zr) nanoparticles in the aluminum matrix provide a high-density heterogeneous nucleation substrate for the T phase. The nucleation energy barrier of the T phase can be significantly reduced, so that a large number of nucleation occurs at a lower temperature; at the same time, the space pinning effect of the L12 phase effectively inhibits the Ostwald ripening of the T phase at high temperature, promotes the precipitation of the T phase in a smaller and more dispersed manner, and significantly improves the strengthening effect of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum alloy technology, specifically relating to an Al-Mn-Cu heat-resistant aluminum alloy with Sc and Zr microalloying, its preparation method and application. Background Technology

[0002] Heat-resistant aluminum alloys are aluminum alloys that can be stably used for a long time in high-temperature environments above 200℃ and have advantages such as high strength, fatigue resistance and good creep resistance. As a result, they are widely used in automobiles, aerospace equipment and other fields.

[0003] Currently, mainstream heat-resistant aluminum alloys on the market are divided into three major systems: Al-Si, Al-Cu, and Al-Mg. However, the service conditions of hot-end components in high-end equipment are gradually increasing to above 300°C. The high-temperature strength and creep resistance of traditional alloy systems rapidly decline, making them unsuitable for demanding high-temperature applications. Taking the typical A380 cast aluminum-silicon alloy as an example, it mainly relies on the CuAl2 phase for strengthening. This phase is prone to rapid coarsening above 250°C, significantly reducing its high-temperature strengthening effect and making it unsuitable for harsh high-temperature service environments of 300°C and above. In recent years, researchers have developed Al-RE rare-earth-based heat-resistant aluminum alloys, which have improved heat resistance. However, the high cost of rare-earth alloy raw materials and the immature theoretical system related to material design and precipitation strengthening limit industrial application. Therefore, it is urgent to develop new heat-resistant strengthening phases with better thermal stability than the traditional CuAl2 phase to overcome the technical bottlenecks of insufficient high-temperature performance and high cost of existing heat-resistant aluminum alloys. Summary of the Invention

[0004] The purpose of this invention is to provide an Al-Mn-Cu heat-resistant aluminum alloy with Sc and Zr microalloying, its preparation method and application, thereby overcoming the shortcomings of the prior art. By adding Sc and Zr elements to the Al-Mn-Cu alloy to form L12-Al3(Sc,Zr) nano-precipitates, the precipitation of T phase is promoted, the high-temperature stability of T phase is improved, and an Al-Mn-Cu alloy with relatively good heat resistance is prepared.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a heat-resistant aluminum alloy, which is composed of the following components by mass percentage: Mn 2.0~4.0%, Cu 1.5~4.0%, Sc 0.2~0.4%, Zr 0.2~0.4%, Cr 0~0.5%, with the balance being aluminum and unavoidable impurities. The addition of Sc and Zr elements forms L12-Al3(Sc,Zr) nano-precipitates to promote the precipitation of T phase.

[0006] In this heat-resistant aluminum alloy, Mn and Cu can form Al with excellent thermal stability within the alloy.20 Cu2Mn3 (T phase) is a heat-resistant strengthening phase that effectively improves the strength and creep resistance at medium and high temperatures. Rare earth Sc and transition metal Zr synergistically precipitate nanoscale Al3(Sc,Zr) dispersed particles, which can strongly pin grain boundaries and dislocations, inhibit grain growth at high temperatures, hinder grain boundary slip, and significantly alleviate the problem of high-temperature softening. Trace amounts of Cr can further refine the as-cast grains, reduce microstructure segregation, and optimize the hot working properties of the alloy.

[0007] Secondly, the present invention provides a method for preparing a heat-resistant aluminum alloy, comprising the following steps: Pure aluminum ingots are heated and melted, and surface impurities are removed to obtain molten aluminum. Pure copper and intermediate alloy are added to the aluminum melt, stirred and mixed, and kept at a constant temperature. The mixture is stirred and mixed again and surface impurities are removed to obtain the alloy melt. The alloy melt is poured and cooled to form an alloy ingot; Heat-resistant aluminum alloy is obtained by aging heat treatment of alloy ingots.

[0008] The preparation method is simple, highly controllable, and easy to industrialize and mass-produce, ultimately producing aluminum alloy materials with uniform structure, low impurity content, and excellent heat resistance.

[0009] Thirdly, this invention provides applications of heat-resistant aluminum alloys in the automotive industry and aerospace components.

[0010] This heat-resistant aluminum alloy can meet the requirements of high-temperature service scenarios above 300°C, and has wide applications, especially in the automotive industry, aerospace and other fields.

[0011] The beneficial effects of this invention are: (1) This invention forms the L12-Al3(Sc,Zr) phase by adding Sc and Zr elements to an Al-Mn-Cu alloy. The L12-Al3(Sc,Zr) nano-precipitates have attracted widespread attention due to their complete coherence with the aluminum matrix. The preferential precipitation of L12-Al3(Sc,Zr) nanoparticles in the aluminum matrix provides a high-density heterogeneous nucleation substrate for the T phase. This significantly reduces the nucleation energy barrier of the T phase, enabling it to nucleate in large quantities at lower temperatures. Simultaneously, the spatial pinning effect of the L12 phase effectively suppresses the Ostwald coarsening of the T phase at high temperatures, promoting the smaller and more dispersed precipitation of the T phase, and significantly improving the alloy strengthening effect.

[0012] (2) This invention uses a copper mold with a small casting opening. During casting, the melt cools rapidly, preventing elements with low equilibrium solubility such as Mn, Cu, Sc, and Zr from precipitating intermetallic compounds. These elements dissolve extensively in the Al matrix, forming a supersaturated solid solution, which facilitates the precipitation of more fine, Mn-rich, dispersed strengthening phases during subsequent aging and inhibits the precipitation of coarse phases. Thorough stirring during melting ensures uniform alloy composition and avoids localized segregation in the ingot. Simultaneously, Sc and Zr elements are added to the alloy, and combined with appropriate heat treatment processes, comparing Al-Mn-Cu alloys and Al-Mn-Cu-0.3Sc-0.3Zr alloys. The study found that after holding the as-cast alloy at room temperature for 1 hour, the hardness of the alloy with added Sc and Zr elements increased rapidly, significantly higher than the alloy without added Sc and Zr elements, and exhibited good thermal stability at 300-450℃. Attached Figure Description

[0013] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0014] Figure 1 The hardness curve of the test alloy under long-term aging at 300℃ is shown. Figure 2 The hardness curve of the test alloy under long-term aging at 350℃ is shown. Figure 3 The hardness curve of the test alloy under long-term aging at 400℃ is shown. Figure 4 The hardness curve of the test alloy under long-term aging at 450℃ is shown. Figure 5 The hardness curve of the Cr-containing test alloy after long-term aging at 450℃ is shown. Detailed Implementation

[0015] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0016] Although existing Al-Mn-Cu alloys contain heat-resistant T phase (Al 20 Cu2Mn3), but it is difficult to precipitate a sufficient amount of dispersed T phase during low-temperature aging, and high-temperature aging above 500℃ will cause the T phase to coarsen rapidly, resulting in a significant decrease in the strengthening effect. It is impossible to balance sufficient precipitation and high-temperature structural stability, which limits the improvement of the alloy's heat resistance.

[0017] This invention introduces the formation of the L12-Al3(Sc,Zr) phase by adding Sc and Zr elements to an Al-Mn-Cu alloy. The L12-Al3(Sc,Zr) nanoprecipitates have attracted widespread attention due to their complete coherence with the aluminum matrix. Their preferential precipitation of L12-Al3(Sc,Zr) nanoparticles within the aluminum matrix provides a high-density heterogeneous nucleation substrate for the T phase. This significantly lowers the nucleation energy barrier of the T phase, enabling it to nucleate extensively at lower temperatures. Simultaneously, the spatial pinning effect of the L12 phase effectively suppresses Ostwald coarsening of the T phase at high temperatures, promoting smaller and more dispersed precipitation of the T phase and significantly enhancing the alloy's strengthening effect.

[0018] In a first aspect, the present invention provides a heat-resistant aluminum alloy, which is composed of the following components by mass percentage: Mn 2.0~4.0%, Cu 1.5~4.0%, Sc 0.2~0.4%, Zr 0.2~0.4%, Cr 0~0.5%, with the balance being aluminum and unavoidable impurities.

[0019] During their research, the inventors discovered that the main strengthening effect of heat-resistant aluminum alloys depends on the nano-sized particles—T' phase (Al2O3) precipitated during the aging process. 20 (Cu2Mn3). Existing heat-resistant aluminum alloys require the addition of Si along with Mg for alloying. For example, in Al-Mg-Si-Mn alloys, a manganese-rich dispersed phase and a transition phase β'-Mg2Si are formed during homogenization. The β'-Mg2Si phase provides preferential nucleation sites for the manganese-rich dispersed phase until it completely disappears, forming a stable manganese-rich dispersed phase. However, the addition of Si will impair the coarsening resistance of the Al3(Sc,Zr) phase. Furthermore, using two Al-Mn-Mg alloys as experimental materials, it was found that the number and volume fraction of the dispersed phase in the manganese-containing alloy were significantly higher than those in the matrix alloy without Mg. This means that the addition of Mg is not a necessary element for the manganese-rich dispersed phase.

[0020] This invention introduces Sc and Zr elements into Al-Mn-Cu alloys. Only when Sc and Zr are fully dissolved into the matrix can L12-Al3(Sc,Zr) nano-precipitates be formed, thereby promoting T-phase precipitation, improving the high-temperature stability of the T-phase, and preparing Al-Mn-Cu alloys with relatively good heat resistance. This invention achieves this condition through thorough stirring during the melting process, and the rapid cooling rate during casting prevents the formation of coarse precipitates. The set aging temperature of 300-450℃ also matches the precipitation temperature range of the L12 phase. This results in a high nucleation rate of fine and dispersed precipitates.

[0021] In some other embodiments, the mass ratio of Cu to Mn is ≥0.75.

[0022] In some other embodiments, the heat-resistant aluminum alloy is composed of the following components by mass percentage: Mn 2.0~4.0%, Cu 1.5~4.0%, Sc 0.3%, Zr 0.3%, Cr 0.5%, with the balance being aluminum and unavoidable impurities.

[0023] In some other embodiments, the heat-resistant aluminum alloy has a hardness of 90-105 HV after aging at 300-400°C and a hardness of 80-130 HV after aging at 450°C.

[0024] Secondly, the present invention provides a method for preparing a heat-resistant aluminum alloy, comprising the following steps: Pure aluminum ingots are heated and melted, and surface impurities are removed to obtain molten aluminum. Pure copper and intermediate alloy are added to the aluminum melt, stirred and mixed, and kept at a constant temperature. The mixture is stirred and mixed again and surface impurities are removed to obtain the alloy melt. The alloy melt is poured and cooled to form an alloy ingot; Heat-resistant aluminum alloy is obtained by aging heat treatment of alloy ingots.

[0025] In some other embodiments, casting is performed using a copper mold with a smaller gating size (mold cavity size 3mm). 15mm (150mm) During casting, the melt is rapidly cooled, so that elements with low solubility under equilibrium, such as Mn, Cu, Sc, and Zr, do not have time to precipitate intermetallic compounds. As a result, they dissolve in large quantities in the Al matrix, forming a supersaturated solid solution. This allows for the precipitation of more fine Mn-rich dispersed strengthening phases during subsequent aging, and can suppress the precipitation of coarse phases.

[0026] In some other embodiments, the purity of the pure aluminum ingot and the pure copper is ≥99.9 wt%.

[0027] In some other embodiments, the master alloy is selected from one or more of Al-10Mn master alloy, Al-2Sc master alloy, Al-5Zr master alloy and Al-10Cr master alloy.

[0028] In some other embodiments, the heating and melting temperature is 700-760°C, and the holding time is 20-30 minutes.

[0029] Specifically, the temperature at which the pure aluminum ingot is heated and melted is any value within the range of 700℃, 730℃, 750℃, and 760℃, and the holding time is any value within the range of 20min, 25min, and 30min.

[0030] Under these conditions, copper and various alloying elements can be uniformly dissolved into the aluminum matrix, significantly improving the uniformity of the melt composition, reducing component segregation and the formation of coarse intermetallic impurity phases, and laying a uniform microstructure foundation for the subsequent precipitation of heat-resistant strengthening phases.

[0031] In some other embodiments, the cooling and forming method is air cooling; air cooling forming eliminates the need for complex cooling media and circulation equipment such as water cooling, simplifying production line configuration and reducing equipment investment and maintenance costs; the air cooling rate is gentle and uniform, which can avoid the defects such as huge internal stress, cracks, porosity and looseness caused by rapid cooling, effectively reducing ingot segregation, ensuring that copper and doped alloying elements are evenly distributed in the aluminum matrix, which is conducive to the stable precipitation of heat-resistant strengthening phases in the subsequent aging process.

[0032] The aging heat treatment temperature is 300~450℃, and the time is 1~60h.

[0033] Specifically, the aging heat treatment was carried out at 300, 350, 400, and 450℃, with holding times ranging from 1 to 60 hours. The aging heat treatment can fully activate the aging strengthening effect, stably generate high-temperature stable nano-precipitates, and simultaneously improve the high-temperature strength and creep resistance of the alloy.

[0034] Thirdly, this invention provides applications of heat-resistant aluminum alloys in the automotive industry and aerospace components.

[0035] The hardness of the alloy increased rapidly after the addition of Sc and Zr elements, which was significantly higher than that of the alloy without the addition of Sc and Zr elements, and the thermal stability at 300~450℃ was good.

[0036] The objective of this invention can be achieved through the following technical solutions: Example 1 A Sc and Zr microalloyed Al-Mn-Cu heat-resistant aluminum alloy is composed of the following components by mass percentage: Mn 2%, Cu 1.5%, Sc 0.3%, Zr 0.3%, with the balance being aluminum and unavoidable impurities.

[0037] The preparation method of the Sc and Zr microalloyed Al-Mn-Cu heat-resistant aluminum alloy is as follows: Using pure Al, pure Cu, Al-10Mn, Al-2Sc, and Al-5Zr master alloys as raw materials, the raw material ratio was determined according to the target alloy composition Al-2Mn-1.5Cu-0.3Sc-0.3Zr.

[0038] Pure aluminum ingots are melted and heated to 750°C. Pure Cu and Al-10Mn, Al-2Sc and Al-5Zr intermediate alloys are added, stirred thoroughly and kept at the temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0039] Example 2 Unlike Example 1, the Sc and Zr microalloyed Al-Mn-Cu heat-resistant aluminum alloy is composed of the following components by mass percentage: Mn 3%, Cu 2.3%, Sc 0.3%, Zr 0.3%, with the balance being aluminum and unavoidable impurities.

[0040] The preparation method of the Al-Mn-Cu heat-resistant aluminum alloy with Sc and Zr microalloying is the same as that in Example 1, and the target alloy obtained is marked as Al-3Mn-2.3Cu-0.3Sc-0.3Zr.

[0041] Example 3 Unlike Example 1, the Sc and Zr microalloyed Al-Mn-Cu heat-resistant aluminum alloy is composed of the following components by mass percentage: Mn 4%, Cu 3%, Sc 0.3%, Zr 0.3%, with the balance being aluminum and unavoidable impurities.

[0042] The preparation method of the Al-Mn-Cu heat-resistant aluminum alloy with Sc and Zr microalloying is the same as that in Example 1, and the target alloy obtained is marked as Al-4Mn-3Cu-0.3Sc-0.3Zr.

[0043] Example 4 Unlike Example 1, the Al-Mn-Cu-Cr microalloyed aluminum alloy with Sc and Zr is composed of the following components by mass percentage: Mn 2.5%, Cu 4%, Sc 0.3%, Zr 0.3%, Cr 0.5%, with the balance being aluminum and unavoidable impurities.

[0044] The preparation method of Al-Mn-Cu-Cr microalloyed heat-resistant aluminum alloys with Sc and Zr is as follows: Using pure Al, pure Cu, Al-10Mn, Al-10Cr, Al-2Sc, Al-5Zr and Al-Cr master alloy as raw materials, the raw material ratio was determined according to the target alloy composition Al-2.5Mn-0.5Cr-4Cu-0.3Sc-0.3Zr.

[0045] Pure aluminum ingots are melted and heated to 750°C. Pure Cu, Al-10Mn, Al-10Cr, Al-2Sc, Al-5Zr and Al-Cr master alloys are added. The mixture is stirred thoroughly and kept at this temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0046] Comparative Example 1 Unlike Example 1, the Al-Mn-Cu alloy with Sc and Zr omitted consists of the following components by mass percentage: Mn 2%, Cu 1.5%, with the balance being aluminum and unavoidable impurities.

[0047] The preparation method of Al-Mn-Cu alloy is as follows: Pure Al, pure Cu, and Al-10Mn master alloy were used as raw materials, and the raw material ratio was determined according to the target alloy composition Al-2Mn-1.5Cu.

[0048] Pure aluminum ingots are melted and heated to 750°C. Pure Cu and Al-10Mn master alloys are added, stirred thoroughly, and kept at the temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0049] Comparative Example 2 Unlike Example 2, the Al-Mn-Cu alloy with Sc and Zr omitted consists of the following components by mass percentage: Mn 3%, Cu 2.3%, with the balance being aluminum and unavoidable impurities.

[0050] The preparation method of Al-Mn-Cu alloy is as follows: Pure Al, pure Cu, and Al-10Mn master alloy were used as raw materials, and the raw material ratio was determined according to the target alloy composition Al-3Mn-2.3Cu.

[0051] Pure aluminum ingots are melted and heated to 750°C. Pure Cu and Al-10Mn master alloys are added, stirred thoroughly, and kept at the temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0052] Comparative Example 3 Unlike Example 3, the Al-Mn-Cu alloy with Sc and Zr omitted consists of the following components by mass percentage: Mn 4%, Cu 3%, with the balance being aluminum and unavoidable impurities.

[0053] The preparation method of Al-Mn-Cu alloy is as follows: Pure Al, pure Cu, and Al-10Mn master alloy were used as raw materials, and the raw material ratio was carried out according to the target alloy composition Al-4Mn-3Cu.

[0054] Pure aluminum ingots were melted and heated to 750℃, then pure Cu and Al-10Mn master alloys were added. The mixture was stirred thoroughly and held at that temperature for 25 minutes. The melt was then poured into a copper mold and cast. Alloy materials with different compositions were prepared.

[0055] Comparative Example 4 Unlike Example 4, the aluminum alloy with added Sc was omitted and consisted of the following components by mass percentage: Mn 2.5%, Cu 4%, Zr 0.3%, Cr 0.5%, with the balance being aluminum and unavoidable impurities.

[0056] The preparation method of aluminum alloy is as follows: Pure Al, pure Cu, Al-10Mn, Al-10Cr, Al-5Zr and Al-Cr master alloy were used as raw materials, and the raw material ratio was set according to the target alloy composition Al-2.5Mn-0.5Cr-4Cu-0.3Zr.

[0057] Pure aluminum ingots are melted and heated to 750°C. Pure Cu, Al-10Mn, Al-10Cr, Al-5Zr and Al-Cr master alloys are added. The mixture is stirred thoroughly and kept at this temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0058] Comparative Example 5 Unlike Example 4, the aluminum alloy with added Zr was omitted and consisted of the following components by mass percentage: Mn 2.5%, Cu 4%, Sc 0.3%, Cr 0.5%, with the balance being aluminum and unavoidable impurities.

[0059] The preparation method of aluminum alloy is as follows: Pure Al, pure Cu, Al-10Mn, Al-10Cr, Al-2Sc and Al-Cr master alloy were used as raw materials, and the raw material ratio was set according to the target alloy composition Al-2.5Mn-0.5Cr-4Cu-0.3Sc.

[0060] Pure aluminum ingots are melted and heated to 750°C. Pure Cu, Al-10Mn, Al-10Cr, Al-2Sc and Al-Cr master alloys are added, stirred thoroughly and kept at the temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0061] Comparative Example 5 revealed that when Sc was added but Zr was not, the generated Al3Sc tended to coarsen and had low particle dispersion, resulting in poor induction of T phase precipitation.

[0062] Comparative Example 6 Unlike Example 4, the aluminum alloy with added Cr was omitted and consisted of the following components by mass percentage: Mn 3%, Cu 4%, Sc 0.3%, Zr 0.3%, with the balance being aluminum and unavoidable impurities.

[0063] The preparation method of aluminum alloy is as follows: Using pure Al, pure Cu, Al-10Mn, Al-2Sc, and Al-5Zr master alloys as raw materials, the raw material ratio was determined according to the target alloy composition Al-3Mn-4Cu-0.3Sc-0.3Zr.

[0064] Pure aluminum ingots are melted and heated to 750°C. Pure Cu and Al-10Mn, Al-2Sc, and Al-5Zr intermediate alloys are added. The mixture is stirred thoroughly and kept at this temperature for 25 minutes. The melt is then poured into a copper mold and cast.

[0065] Comparative Example 7 Unlike Example 3, the Mg-added heat-resistant aluminum alloy consists of the following components by mass percentage: Mn 4%, Cu 3%, Mg 2.5%, Sc 0.3%, Zr 0.3%, with the balance being aluminum and unavoidable impurities. The preparation method of this aluminum alloy is the same as in Example 3, and the resulting target alloy is designated Al-4Mn-3Cu-2.5Mg-0.3Sc-0.3Zr.

[0066] Comparative Example 7 showed that adding Mg can improve the strength of the alloy by utilizing its solid solution strengthening or age hardening effects. However, the heat resistance limit of the alloy is generally around 225℃. Above the heat resistance limit temperature, the Mg-containing precipitates (such as Mg2Si and S phases) will rapidly coarsen, leading to a rapid decrease in the high-temperature strength of the alloy.

[0067] This invention does not contain Mg and relies on the T phase (Al) 20 The synergistic strengthening effect of Cu2Mn3 and L12-Al3(Sc,Zr) nanoparticles results in a high-temperature stability that is far superior to that of Mg-containing precipitates. Therefore, the alloy exhibits higher hardness retention and better thermal stability after long-term aging at 300–450 °C. The primary Al3(Sc,Zr) phase formed by Sc and Zr may provide nucleation sites for Mg-containing compounds, inhibiting recrystallization and refining the grain size of the as-cast alloy. This consumes the Sc and Zr solutes originally used to form L12-Al3(Sc,Zr) nanoparticles, reducing the effective utilization rate of microalloying elements. In Mg-free systems, Sc and Zr can more fully form the L12 phase, resulting in higher strengthening efficiency.

[0068] Performance testing Samples were taken from the as-cast alloys prepared in the examples and comparative examples, and the samples were placed in a muffle furnace for aging treatment at 300℃, 350℃, 400℃ and 450℃ for 0~60h.

[0069] Hardness Testing: The heat-treated alloy samples were subjected to Vickers hardness testing under a test force of 500 gf. This involved cutting the sample to a suitable size, placing it on the Vickers hardness stage, adjusting the focus to ensure a clear view of the surface, and using a test force of 500 gf and a holding time of 30 seconds. Each data point is the average of six individual measurement points at random locations on the sample surface. Six different locations were tested for each sample to obtain the hardness data.

[0070] Specifically, samples of the cast alloy were taken sequentially. First, the Vickers hardness of the samples at room temperature was tested with a test force of 500 gf. The alloy samples were then placed in a box-type muffle furnace for high-temperature thermal stabilization aging treatment, with heat treatment temperature gradients of 300℃, 350℃, 400℃, and 450℃. At each temperature, aging was performed for 1 hour, 3 hours, 5 hours, 10 hours, 20 hours, 40 hours, and 60 hours starting from 0 min. After each aging treatment, the samples were removed and cooled to room temperature, and then Vickers hardness tests were conducted to obtain the hardness data of the alloy under the corresponding heat exposure conditions. The test results are shown below. Figures 1-4 .

[0071] like Figure 1 As shown, there was no significant difference in hardness among alloys of various compositions at room temperature. However, after aging at 300℃ for 1 hour, the hardness of Al-2Mn-1.5Cu (Example 1) and Al-3Mn-2.3Cu (Example 2) alloys with added Sc and Zr elements increased significantly, by 14.3 HV (Comparative Example 1) and 8.5 HV (Comparative Example 2) respectively, compared to the alloys without added Sc and Zr elements. After reaching the peak hardness at 5 or 10 hours, the hardness remained almost unchanged. However, compared to Al-4Mn-3Cu-0.3Sc-0.3Zr alloy (Example 3) and Al-4Mn-3Cu alloy (Comparative Example 3), the hardness value did not increase significantly, and the hardness also remained almost unchanged after 5 or 10 hours of aging. This is because a higher temperature is required to precipitate more solute atoms from the supersaturated solid solution, forming more and finer dispersed heat-resistant phases Al3Sc / Al3Zr. Obviously, 300℃ has not yet reached its saturation precipitation temperature.

[0072] like Figure 2 As shown, similarly, after aging at 350℃ for 1 hour, Al-2Mn-1.5Cu-0.3Sc-0.3Zr (Example 1) and Al-3Mn-2.3Cu-0.3Sc-0.3Zr (Example 2) showed significantly higher maximum hardness than Al-2Mn-1.5Cu (Comparative Example 1) and Al-3Mn-2.3Cu (Comparative Example 2), with increases of 40 HV and 25.2 HV, respectively. The Al-4Mn-3Cu-0.3Sc-0.3Zr alloy (Example 3) also showed some improvement compared to the Al-4Mn-3Cu alloy (Comparative Example 3), with a maximum hardness increase of 8.3 HV.

[0073] like Figure 3 As shown, after aging at 400℃ for 1 hour, the maximum hardness of the alloys with added Sc and Zr increased by 35.9 HV, 22.1 HV, and 11.3 HV, respectively, compared to those without added Sc and Zr. Figure 4 As shown, the maximum hardness increased by 44.3 HV, 25.5 HV, and 13.2 HV respectively upon aging at 450℃. The results indicate that the strengthening effect of the combined addition of Sc and Zr elements in the Al-Mn-Cu alloy is superior to that of the Al-Mn-Cu alloy without the addition of Sc and Zr elements.

[0074] The alloys obtained in Example 4 and Comparative Example 6 were aged at 450°C. After holding at this temperature for a certain time, the samples were cooled to room temperature, and their Vickers hardness was tested. The test force was 500 gf, and the holding time was 30 s. The resulting curves showing the relationship between aging time and alloy hardness were obtained. Figure 5 As shown, the addition of Cr increases the hardness of the alloy, indicating that Cr is beneficial for improving the heat resistance of the alloy.

[0075] The as-cast alloys obtained in the examples and comparative examples were subjected to tensile strength and elongation tests, and the results are shown in Table 1. The tensile strength and elongation test method involved cutting standard plate-shaped tensile specimens using a wire EDM machine, placing the specimens in a muffle furnace, and aging them at 400℃ for 5 hours. The original gauge length L0 = 20 mm was marked, and the thickness and width of the specimens were measured. After heat treatment, the specimens were placed in the chucks of a material testing machine, clamped vertically, and the maximum load was recorded to calculate the tensile strength. After fracture, the specimens were spliced ​​together, the gauge length after fracture was measured, and the elongation after fracture was calculated.

[0076] Table 1. Results of tensile strength and elongation tests

[0077] As shown in Table 1, the alloys without Sc and Zr (Comparative Examples 1-3) have lower strength, while the strength of the alloys with the addition of Sc and Zr (Examples 1-3) increases significantly. This indicates that Sc and Zr can promote the formation of precipitated phases, thereby improving the alloy strength.

[0078] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A heat-resistant aluminum alloy, characterized in that, The composition by mass percentage is as follows: Mn 2.0~4.0%, Cu 1.5~4.0%, Sc 0.2~0.4%, Zr 0.2~0.4%, Cr 0~0.5%, with the balance being aluminum and unavoidable impurities. The addition of Sc and Zr elements forms L12-Al3(Sc,Zr) nano-precipitates, which promote the precipitation of the T phase.

2. The heat-resistant aluminum alloy according to claim 1, characterized in that, The mass ratio of Cu to Mn is ≥0.

75.

3. The heat-resistant aluminum alloy according to claim 1, characterized in that, It consists of the following components by mass percentage: Mn 2.0~4.0%, Cu 1.5~4.0%, Sc 0.3%, Zr 0.3%, Cr 0.5%, with the balance being aluminum and unavoidable impurities.

4. The heat-resistant aluminum alloy according to claim 1, characterized in that, The hardness of heat-resistant aluminum alloys after aging at 300~400℃ is 90~105HV, and the hardness after aging at 450℃ is 80-130 HV.

5. A method for preparing the heat-resistant aluminum alloy according to any one of claims 1-4, characterized in that, Includes the following steps: Pure aluminum ingots are heated and melted, and surface impurities are removed to obtain molten aluminum. Pure copper and intermediate alloy are added to the aluminum melt, stirred and mixed, and kept at a constant temperature. The mixture is stirred and mixed again and surface impurities are removed to obtain the alloy melt. The alloy melt is poured and cooled to form an alloy ingot; Heat-resistant aluminum alloy is obtained by aging heat treatment of alloy ingots.

6. The method for preparing the heat-resistant aluminum alloy as described in claim 5, characterized in that, The purity of the pure aluminum ingots and pure copper is ≥99.9wt%.

7. The method for preparing the heat-resistant aluminum alloy as described in claim 5, characterized in that, The master alloy is selected from one or more of Al-10Mn master alloy, Al-2Sc master alloy, Al-5Zr master alloy and Al-10Cr master alloy.

8. The method for preparing the heat-resistant aluminum alloy as described in claim 5, characterized in that, The heating and melting temperature is 700~760℃, and the holding time is 20~30min.

9. The method for preparing the heat-resistant aluminum alloy as described in claim 5, characterized in that, The cooling and molding method is air cooling; The aging heat treatment is performed at a temperature of 300~450℃ for a time of 1~60h.

10. The application of the heat-resistant aluminum alloy according to any one of claims 1-4 in the automotive industry and aerospace devices.